Defensive egotism and self-esteem: A cross-cultural examination of the dynamics of bullying in middle school*. Issue 3 (4th May 2017) - Simon, Joan B.; Nail, Paul R.; Swindle, Taren; Bihm, Elson M.; Joshi, Keyoor
Abstract: The revised compensation model of aggression posits that bullying is driven by defensive personality, not low self-esteem. Supporting research has failed to distinguish bullies vs. bully-victims (i.e., bullies who are also victims). In three studies with middle school students on two continents, pure bullies and bully-victims scored higher in defensive egotism than pure victims and controls but, unexpectedly, did not differ from each other. Low self-esteem was linked with victimization, high self-esteem with defending victims. Boys were higher than girls in bullying and physical aggression; girls were higher in social than physical aggression. Part of the lack of success of anti-bullying programs may be their failure to accommodate different types of bullies and different forms of bullying.